(untitled) (The Planet, 2024)
Introduction: Visual Inspection with Acetic Acid (VIA) is a crucial cervical cancer screening method that has proven to be an effective and accessible tool, particularly in resource-limited settings. Cervical cancer is a significant global health concern, with a disproportionately high burden in low- and middle-income countries. In the absence of widespread access to more sophisticated screening technologies, VIA has emerged as a valuable technique for early detection and management of cervical abnormalities. Objective: To determine the frequency CIN I, CIN II, CIN III in Visual Inspection with Acetic Acid (VIA) positive cases with the help of colposcopic examination. Methods and materials: The was prospective cross sectional descriptive study conducted among the Visual Inspection with Acetic Acid (VIA) positive cases who were attending at in Colposcopic Clinic of Department of Obstetrics and Gynecology, BSMMU, Dhaka, Bangladesh during 1st June 2010 to 30th August 2010. Results: The mean age was 35.8±9.9 years and majority (40.0%) subjects were found between 30-39 years age group. Most (72.0%) of the study patients were multipara and the mean age of ’last confinement was 7.8±6.8 years. Majority 38(38.0%) of the patient was normal, 25(25.0%) of the study patients had CIN I, CIN II in 13(13.0%), CIN III in 5(5.0%), 4(4.0%) had invasive carcinoma and 15(15.0%) unsatisfactory Colposcopy. Conclusions: Visual inspection with acetic acid (VIA) effective to screen women. It can be done by nurses or midwives with appropriate training. Although still under investigation, research results show that VIA is simple, accurate, cost-effective, and acceptable to most women.